Pycnidial Septoria-like micromycetes of Belarus. First addition to the list of species - Fiadziushka, Ilya А. (Experimental Biology and Biotechnology, 2025)
The article reports the findings of 26 new species of pycnidial Septoria-like micromycetes to the territory of Belarus from the genera Septoria, Sphaerulina, Phaeoseptoria and Rhabdospora. Descriptions and illustrations are provided of the identified species of pycnidial Septoria-like micromycetes. The species Septoria alliariae, S. astericola, S. crataegophila, S. endiviae, S. erysimi, S. matricariae, S. sisymbrii, S. sleumeri, Sphaerulina oxyacanthae, Rhabdospora intybi is considered alien to the mycobiota of Belarus. Based on the structural features of conidiomata, it is suggested that species Septoria crataegophila and Sphaerulina oxyacanthae should be included in the group of acervular Septoria-like micromycetes.
Keywords: fungi; pycnidial Septoria-like micromycetes; Herbarium of the Belarusian State University; MSKU; Septoria; Sphaerulina; Phaeoseptoria; Rhabdospora; native component of the mycobiota; alien component of the mycobiota; host plant; Belarus